Circles of Influence: The Role of School-Community Partnerships in the Character Formation and Citizenship of Secondary School Students - Hands, Catherine M. (Alberta Journal of Educational Research, 2008)
Partnerships between schools, families, and communities provide a support net for each student and play a role in promoting academic success (Epstein, 1995; Shapiro, Ginsberg, & Brown, 2002) and moral development. This article is based on a qualitative study of a secondary school with numerous partnerships selected from a southern Ontario school board characterized by economic and cultural diversity. Drawing on the analysis of archival data, observations, and 19 interviews with the educators and community partners at one of the schools, it was found that the study participants shared an understanding of education as the joint responsibility of the school and the community. This article discusses the partnership practices and in so doing, the roles of community partners in encouraging moral development by supporting students academically, emotionally, and socially. When community partners provided learning opportunities and resources not available in the school, the students enhanced their skill sets and were exposed to diverse community values. Through partnership activities, civic responsibility was promoted, and students’ social capital was strengthened as they established their own links with the community in which they lived.